Arborização rural: perspectivas conceituais e estudo de caso em Araras-SP - Brandino, Noelle de Cássia (2022)
The study of rural territorial space is not only synonymous with agriculture, but it should also seek to understand issues of sustainability and rural development, including issues such as rural afforestation. Thus, the present work aimed to identify references about afforestation in different spaces of the rural environment, through a bibliographical and documental review. References and sources consulted indicate that trees are components of the rural landscape, giving authenticity and providing shading to community spaces; increase in organic matter content; by attenuating wind speed, they protect the soil from erosion; conserve soil moisture; produces wood and fruit; can be used as hedges and windbreaks. It was concluded, therefore, that although afforestation has an essential role in rural areas, there are very few studies focusing on the theme, with studies focused on the urban environment being widely found. From the point of view of agroecology, there are examples of the use of tree species in productive spaces and in agroecological backyards, but not identifying the diversity of species used to compose these spaces. Studies with a rural development approach mention the plurality of the rural environment, but the afforestation of these spaces is not directly mentioned. For both paradigms, the results obtained mention the theme, but do not portray the intention of afforestation in rural areas, which is, then, a very relevant work to stimulate further research on the subject.